Prarancangan Pabrik Metil Metakrilat dari Aseton Sianohidrin Kapasitas 63.000 Ton/Tahun - Nugroho, Wahyu (2016)
Methyl methacrylate is a chemical in the industry are derived from ester derivative and one form of acrylic resin monomer. Methyl methacrylate is widely used in the industries of paint, resin, household appliances, cosmetics, and polymers. Needs methyl methacrylate in Indonesian is still imported from abroad (imports) and tended to increase each year. Therefore, the establishment of methyl methacrylate plant in Indonesian is very important to reduce imports. Factory methyl methacrylate is expected to meet domestic demand and the possibility to be exported. The process manufacture of methyl methacrylate by the hydrolysis reaction of acetone cyanohydrin and sulfuric acid into metakrilamid sulfate. Then metakrilamid sulfate esterification with methanol to produce methyl methacrylate with byproduct ammonium bisulfate. Both of these processes is reacted in the continuous flow stirred tank reactor (CSTR) and reacted in the liquid phase conditions. The hydrolysis reaction is set at a temperature of 130ºC and a pressure of 1 atm, while the esterification reaction is set at a temperature of 150ºC and a pressure of 7 atm. Methyl methacrylate product purification using distillation and decantation process, so that the resulting product with a purity of 99.8%. Factory methyl methacrylate is designed with a capacity of 63,000 tons/year in operation for 330 days/year. The factory employed about 160 workers, require raw materials acetone cyanohydrin as much as 61,177.32 tons/year, as much sulfuric acid 67,073.05 tons/year, and methanol as much as 21,645.35 tons/year. Unit utility as supporting the production process requires as much water 47,779.68 kg/hour supplied from the Bengawan Solo river, saturated steam as much as 51,599,901.73 kJ/hour supplied from fuel boiler with fuel oil as much as 640.49 liters/hour, needs 750 kW electric power is supplied from PLN and generator set as a backup, and the compressed air requirement of 91.37.m3/hour. Based on economic analysis, methyl methacrylate plant requires a fixed capital of Rp. 768,667,006,796.33 and working capital of Rp.522,362,960,248.84. Profits earned before tax of Rp. 532,161,308,204.95 annually. Profits after tax of Rp. 334,193,727,030.00 annually. The results of the feasibility analysis states that the percent return on investment (ROI) before tax amounted to 62.11% and after tax of 43.48%. Pay out time (POT) before taxes of 1.4 years, while after tax of 1.9 years. Break even point (BEP) amounted to 58.61% of capacity, and shut down point (SDP) amounted to 31.89% of capacity. Discounted cash flow (DCF) of 38.06%. Based on the analysis with these parameters, so the factory methyl methacrylate can be declared eligible to set up in Indonesian.